Knowledge of Iraqi girls towards polycystic ovary syndrome - Raghad Nasif Jasim; Sajidah Saadoon Oleiwi (Kashan University of Medical Sciences, 2023)
Background: Polycystic ovary syndrome (PCOS) affects about 10% of adolescent girls worldwide. However, a study found that almost half of the women had poor knowledge about PCOS.Objectives: This study aimed to assess the knowledge of Iraqi adolescent girls about PCOS.Methods: A cross-sectional study was conducted in October 2022 on a convenient sample of 60 adolescent girl students at the Economic and Administration College of the University of Kerbala, Iraq. Data were collected using a specific questionnaire and analyzed using inferential and descriptive statistics.Results: The mean score of participants knowledge about PCOS was 2.05±1.4 (range:0-7), and all of them had poor knowledge about PCOS. Most participants had no information about PCOS and the remaining received information about PCOS from media (21.3%), educational courses (3.3%), and health institutions (8.2%).Conclusion: Iraqi adolescent girls had low knowledge about PCOS. Counseling and education programs can be established for all women of childbearing age, and especially adolescent girls and university students, to increase knowledge about polycystic ovarian syndrome.